(untitled) (Journal of economic and management development research, 2026)
How to achieve the mutual development between the healthy growth of young people and the steady development of cities is the focus of building a youth-development-oriented city. As an important link for urban development, innovation and entrepreneurship talent policies will directly affect talent agglomeration and the driving force of urban development. Taking Wuhu City as the research object and from the perspective of building a youth-development-oriented city, this paper systematically sorts out the relevant innovation and entrepreneurship talent policies in Wuhu. From the initial exploration of talent cultivation to the iterative upgrade of relevant policies, this paper summarizes the achievements in talent agglomeration and industrial upgrading since the implementation of the policies. Meanwhile, it points out the existing challenges such as insufficient precise matching and imperfect long-term mechanism, puts forward reasonable optimization paths, and provides new development directions and reliable references for other similar cities to promote the construction of youth-development-oriented cities.